ОИЛАДА ЎСМИРЛАРНИ ХАЛҚ ОҒЗАКИ ИЖОДИ АСОСИДА ТАРБИЯЛАШНИНГ ТАРИХИЙ ИЛДИЗЛАРИ - Досходжаева, А. (SCIENCE and SOCIETY, 2023)
This article discusses the issues of the holy book of Zoroastrianism Avesta, the ideas of thinkers about family education, the pedagogical ideas of our scientists about upbringing children in the family, are of great importance to increase the effectiveness of rearing.
Keywords: Avesta; family; teenagers’ upbringing in the family; folklore; scientists’ points of view about family upbringing